Policing Ethics: Context Bangladesh - Adil, Md. Sharifur Rahman (Bangladesh Journal of Bioethics, 2020)
The police are one of the most powerful and important forces for any country. The main task of the police is to install a sense of security in the ordinary citizens and to protect their life and property when they are in danger. Bangladeshi Police have a glorious past with tremendous achievement. Especially in our great liberation war in 1971, they played an important role in achieving our liberation. Eliminating terrorism & militancy and others several operation that leads with the risk of their life. But there are still a lot of accusations against the police force. Like- abusing of power, misconducting with the people, committing crossfire defying the high-court order, wearing white dress when they move to detain criminals, arresting without warrant, and many other including bribery, extortion, trading drug and yaba, playing partisan role, keeping bad association, filing case against deceased man, charging sheet against the infant who has not been born yet, enforcing disappearance, suppressing the freedom of express, violating human rights, doing anti-social activities such as rape, forcible extortion, drinking alcohol, etc. are the real scenario of Bangladesh Police. Policing ethics or related unethical behaviors, in particular, are shaped by both societal perceptions and organizational socialization of the police personnel on how authority should be exercised, as well as the latter's relationship with the socio-political and economic structures overtime. This paper proposes to explain the role of police as the main law enforcement agency in any democratic country. An attempt has been made to bring different perspectives of ethics which comprises views of Aristotle, Machiavelli, Immanuel Kant, J S Mill and John Rawls. The paper focuses on police ethics. Police ethics’ reflects the society and the regulations that shape the policing system. This paper also discuss the results and analysis of the consequences of moral degradation caused by the police. This article explore the police brutality because of the lack of ethics and highlight the public's attitude towards police as well. The ethical standards and the code of conduct of Police practitioners should actually abide by is an ongoing debate.